Retention in Care among HIV-Infected Pregnant Women in Haiti with PMTCT Option B - Jodie Dionne-Odom; Courtney Massaro; Kristen M. Jogerst; Zhongze Li; Marie-Marcelle Deschamps; Cleonas Junior Destine; Redouin Senecharles; Moleine Moles Aristhene; Joseph Yves Domercant; Vanessa Rouzier; Peter F. Wright (AIDS Research and Treatment)
Background. Preventing mother-to-child transmission of HIV relies on engagement in care during the prenatal, peripartum, and postpartum periods. Under PMTCT Option B, pregnant women with elevated CD4 counts are provided with antiretroviral prophylaxis until cessation of breastfeeding. Methods. Retrospective analysis of retention in care among HIV-infected pregnant women in Haiti was performed. Logistic regression was used to identify risk factors associated with loss to follow-up (LFU) defined as no medical visit for at least 6 months and Kaplan-Meier curves were created to show LFU timing. Results. Women in the cohort had 463 pregnancies between 2009 and 2012 with retention rates of 80% at delivery, 67% at one year, and 59% at 2 years. Among those who were LFU, the highest risk period was during pregnancy (60%) or shortly afterwards (24.4% by 12 months). Never starting on antiretroviral therapy (aRR 2.29, 95% CI 1.4–3.8) was associated with loss to follow-up. Conclusions. Loss to follow-up during and after pregnancy was common in HIV-infected women in Haiti under PMTCT Option B. Since sociodemographic factors and distance from home to facility did not predict LFU, future work should elicit and address barriers to retention at the initial prenatal care visit in all women. Better tracking systems to capture engagement in care in the wider network are needed.